2020
DOI: 10.1111/cei.13500
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and roles of severe acute respiratory syndrome coronavirus 2-specific antibodies in patients with different severities of coronavirus 19

Abstract: In order to quantify the levels of SARS‐CoV‐2‐specific IgM, IgA, and IgG antibodies, identify changes in them based on COVID‐19 severity, and establish the significance of combined antibody detection, a chemiluminescence method was used to detect the levels of SARS‐CoV‐2‐specific antibodies in COVID‐19 patients with different severity. We concluded that detection of SARS‐CoV‐2‐specific combined IgA–IgG antibodies is advantageous in diagnosing COVID‐19 and more attention should be paid to specific IgA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 24 publications
(30 reference statements)
8
36
0
3
Order By: Relevance
“…These results indicate that IgA and especially IgA2 antibodies against SARS-CoV-2 may be a better immunologic indicator for severe disease compared to IgG antibodies. This hypothesis is in accordance with studies describing higher SARS-CoV-2-specific, but also total, IgA levels in patients with severe COVID-19 compared to patients with moderate disease [ 25 , 26 ]. Antibody class switches from IgG to IgA1 or IgA2 are a frequent phenomenon [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that IgA and especially IgA2 antibodies against SARS-CoV-2 may be a better immunologic indicator for severe disease compared to IgG antibodies. This hypothesis is in accordance with studies describing higher SARS-CoV-2-specific, but also total, IgA levels in patients with severe COVID-19 compared to patients with moderate disease [ 25 , 26 ]. Antibody class switches from IgG to IgA1 or IgA2 are a frequent phenomenon [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the development of SARS-CoV-2-specific IgA2 may indicate a state of immune dysregulation associated with severe COVID-19. Overall, SARS-CoV-2-specific IgA seems to have a more dynamic course than IgG as it has also been shown that IgA specific for SARS-CoV-2, as well as SARS-CoV, disappears faster than the respective IgG [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we failed to find any difference when blood samples were stratified for time since the onset of symptoms. The same evidence has been highlighted in the studies conducted by Huang and collegues and Hasan Ali and collegues where a higher IgA response was observed in critical and more sever patients [34,35].…”
Section: Discussionsupporting
confidence: 73%
“…In details, the production of SARS-CoV-2-specific IgA has been reported in the serum of seroconverting individuals in the first week after symptoms onset ( Padoan et al, 2020 ; Dahlke et al, 2020 ), IgA appeared first ( Huang et al, 2020 ) and were found in higher amount than IgG in the early stage of the infection ( Infantino et al, 2020 ). Furthermore, IgA levels were correlated to severity of the disease ( Huang et al, 2020 ). The IgA are transported in the mucus via transepithelial transport and could be present in saliva or oral fluid, where they are the main antibody isotype present ( Guo et al, 2020 ; Ceron et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that serum IgA are produced with time-dependent kinetics and in larger amounts than IgM ( Dahlke et al, 2020 ; Yu et al, 2020 ), suggesting that IgA may be useful in the serological characterization of COVID-19-infected individuals and as an alternative and more reliable biomarker of early COVID-19 infection compared to IgM. In details, the production of SARS-CoV-2-specific IgA has been reported in the serum of seroconverting individuals in the first week after symptoms onset ( Padoan et al, 2020 ; Dahlke et al, 2020 ), IgA appeared first ( Huang et al, 2020 ) and were found in higher amount than IgG in the early stage of the infection ( Infantino et al, 2020 ). Furthermore, IgA levels were correlated to severity of the disease ( Huang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%